A meta-ethnography of out-of-hospital cardiac arrest survivors' meanings on life and death - Aristidou, Maria; Vouzavali, Fotini; Karanikola, Maria; Lambrinou, Ekaterini; Papathanassoglou, Elizabeth (My University, 2018)
Background: Although out-of-hospital cardiac arrest (OHCA) survivors' physiological outcomes have been addressed, less is known on the holistic needs of individuals after OHCA, which hinders our ability to prioritize care around what really matters to survivors. Aim: The aim of this study was to interpretatively synthesize qualitative findings on OHCA survivors' perceptions and meanings of life and death and existential issues. Methods: We used a meta-ethnographic synthesis of published qualitative studies addressing the experiences of OHCA survivors based on a systematic literature search (CINAHL, PsycINFO, Scopus, PubMed). Studies were selected based on predefined inclusion/exclusion criteria. The identified studies were subjected to a quality appraisal based on the Critical Appraisal Skills Programme. Results: Based on eligibility criteria, 6 phenomenological studies were included, of overall medium to high quality. One core theme, "the reality of death," and 4 main themes were identified: "redefining existence"; "revaluing death"; "being familiar with, yet oblivious of death"; and "living consciously." Emerging from the realization of death, the themes appeared to describe a gradual progression toward living consciously. Conclusions: An existential trajectory and a need for meaning are central in the experience of OHCA survivors. When existential issues are not addressed, the ongoing suffering may interfere with survivors' recovery and quality of life. Future research needs to address specific needs and ways to support survivors' meaning-making.
Keywords: Death; Existential suffering; Meta-ethnography; Out-of-hospital cardiac arrest; Systematic review